Oxidative stress and use of antioxidants in fish semen cryopreservation - Leydy Sandoval‐Vargas; Mauricio Silva Jiménez; Jennie Risopatrón González; Elías Figueroa Villalobos; Elsa Cabrita; Iván Valdebenito Isler (Reviews in Aquaculture, 2021)
Reactive oxygen species (ROS) have been proposed as one of the main causes of the impairment of fish spermatozoa integrity and functionality during cryopreservation. The high content of unsaturated fatty acids in sperm cells and the low antioxidant capacity of diluted semen are key factors in making sperm cells susceptible to ROS attacks. For this reason, some recent studies have determined the antioxidant status of the seminal plasma and spermatozoa of fish species. Additionally, some studies have evaluated the effects of antioxidants on post‐thaw sperm quality. Although ROS are certainly involved in sperm damage, other factors, such as ice crystal formation, seem to play a crucial role in cryodamage. This challenge has not yet been resolved because both the endogenous antioxidant capacity of the semen and its response to different supplementation practices seem to present specific inter‐ and intraspecies characteristics and effects. This review summarises knowledge on antioxidant defence and oxidative stress in fish semen, as well as antioxidant supplementation in cryopreservation media, in order to establish perspectives for future studies.

New developments and biological insights into the farming of Solea senegalensis reinforcing its aquaculture potential - Sofia Morais; Cláudia Aragão; Elsa Cabrita; Luís E.C. Conceição; Maria Constenla; Benjamín Costas; Jorge Dias; Neil Duncan; Sofia Engrola; Alicia Estevez; Enric Gisbert; Evaristo Mañanós; et al. (Reviews in Aquaculture, 2016)
Senegalese sole was one of the earliest identified candidate species with high potential for aquaculture diversification in the south of Europe. Its culture has been possible, and commercially attempted, for several decades, but intensive production has been slow to take off. This has been explained mostly by serious disease problems, high mortality at weaning, variable growth and poor juvenile quality. However, a strong and sustained research investment that started in the eighties has led to a better understanding of the requirements and particularities of this species. More recently, better management and technical improvements have been introduced, which have led to important progress in productivity and given a new impetus to the cultivation of Senegalese sole. As a result, the last 5 years have marked a probable turning point in the culture of sole towards the development of a knowledge‐driven, competitive and sustainable industry. This review will focus on the main technical improvements and advances in the state of knowledge that have been made in the last decade in areas as diverse as reproductive biology, behaviour, physiology, nutritional requirements, modulation of the immune system in response to environmental parameters and stress, and characterization and mitigation of the main disease threats. It is now clear that Senegalese sole has important particularities that differentiate it from other current and candidate marine aquaculture species, which bring about important challenges, some still unsolved, but also notable opportunities (e.g. a nutritional physiology that is better adapted to dietary vegetable ingredients), as will be discussed here.

Gamete quality and broodstock management in temperate fish - Herve Migaud; Gordon Bell; Elsa Cabrita; Brendan McAndrew; Andrew Davie; Julien Bobe; M.P. Herráez; Manuel Carrillo (Reviews in Aquaculture, 2013)
The ability to fully control sexual maturation and spawning and to produce large numbers of high quality seeds ‘on demand’ (i.e. all year long) is a primary requirement for the successful development of aquaculture. This relies on optimal broodstock management practices based on extensive knowledge of the nutritional and environmental requirements of fish in captivity. However, for many established, emerging and new farmed fish species, such knowledge is limited or not available yet. The level of domestication also plays an essential role as stocks with improved traits in farming conditions are selected. Importantly, reliable indicators of egg quality are still lacking and hatcheries still rely on wild harvested broodstocks in many farmed fish species. These key challenges must be addressed urgently to ensure the sustainable development of the E uropean fish farming sector. This review gives an overview of methods to assess egg/sperm quality and many of the most important factors affecting gamete production and quality, including broodstock nutrition, environmental and spawning induction protocols, genetic management, gamete preservation and new reproductive strategies.